1772. Evaluating the Impact of a Pilot Structured Antimicrobial Stewardship Prospective Audit and Feedback Program in Emergency General Surgery in a Community Hospital. (15th December 2022) - Nisenbaum, Rosane; Tsang, Melanie; Langford, Bradley J; Wan, Michael; Downing, Mark; Chan, April J
Abstract: Background: The benefits of prospective audit and feedback (PAF) are established in critical care settings but not in the surgical population. We piloted once-weekly structured face-to-face PAF with the Acute Care Surgery (ACS) Service surgeon(s) and compared outcomes to usual care which comprised of ad-hoc PAF on targeted antimicrobials once or twice weekly with recommendations made to ACS surgeon(s) using written or verbal methods. Methods: Interrupted time series segmented negative binomial regression analysis was used to evaluate the change in the primary outcome of antimicrobial usage measured in Days of Therapy/1000 patient days (DOT/1000-PD) for all systemic and targeted antimicrobials ordered by the ACS team. The structured PAF period was from August 1, 2017- April 30, 2019 while the ad-hoc PAF period was from May 1, 2019-January 31, 2021. Targeted antimicrobials included 3 rd generation cephalosporins, piperacillin/tazobactam, carbapenems and clindamycin. Secondary outcomes included C. difficile infections, length of stay and readmission within 30 days. The first two secondary outcomes were analyzed using a logistic regression model while a negative binomial regression model was used to evaluate readmission within 30 days. Results: There were 776 ACS patients in the structured PAF period with 783 patients in the ad-hoc PAF period. = No significant changes in level or trend of the primary outcome of DOT/1000-PD in both periods was found for all and targeted antimicrobials. However, there was a trend to small reduction in DOT/1000-PD of 0.9% per month (rate ratio 1.0, CI 0.99-1.02) for all antimicrobials and 0.3% per month (rate ratio 1.0, CI 0.98-1.03) for targeted antimicrobials in the ad-hoc PAF period. Similarly, there were no significant differences with respect to any of the secondary outcomes. There was a trend of 10% increase in length of stay (rate ratio 1.07, CI 0.98-1.17) and 13% reduction in 30-day readmission (OR 0.87, CI 0.56-1.35) in the ad-hoc PAF period. Rates by Time Using Negative Binomial Models for All and Targeted Antimicrobials Conclusion: Structured PAF showed similar clinical outcomes to ad-hoc PAF for the Acute Care Surgery Service at our institution. Other antimicrobial stewardship interventions can be explored to better support judicious antimicrobial use in General Surgery. Disclosures: All Authors : No reported disclosures.